The Motivational Hierarchy between the Personal Self and Close Others in the Chinese Brain: an ERP Study - Zhu, Xiangru; Wang, Lili; Yang, Suyong; Gu, Ruolei; Wu, Haiyan; Luo, Yuejia (Frontiers in Psychology, 2016)
People base their decisions not only on their own self-interest but also on the interests of close others. Generally, the personal self has primacy in the motivational hierarchy in the Western culture. A recent study found that friends have the same motivational hierarchy as the personal self in the Eastern collectivist culture. Remaining unknown is whether the motivational hierarchy of the personal self and close others can be manifested in the collectivist brain. In the present study, we asked participants to gamble for the personal self, close others (i.e., mother, father, and close friend), and strangers. The positive-going deflection of event-related potentials (ERPs) in response to positive feedback showed the following pattern: personal self = mother = father > friend > stranger. In the loss condition, no significant beneficiary effect was observed. The present results indicate that the personal self and parents are intertwined in the motivational system in the Chinese undergraduate student brain, supporting the view that the personal self and parents have the same motivational primacy at the electrocortical level.